Plastome-based phylogeny and biogeography of Lactuca L. (Asteraceae) support revised lettuce gene pool categories - Chu, Ran; Xu, Xuemin; Lu, Zhenwei; Ma, Yonggui; Cheng, Han; Zhu, Shixin; Bakker, Freek T.; Schranz, M. Eric; Wei, Zhen (Frontiers in Plant Science, 2022)
This study generated and analyzed complete plastome and ITS data of 46 Lactuca species plus 13 African endemic (AE) Lactuca species as well as 15 species from eight related genera in Lactucinae. The new plastome and nuclear ITS sequences were then used to reconstruct the phylogenetic relationships of Lactuca species. The whole plastome data was used to estimate divergence time and ancestral area reconstruction of the major identified Lactuca lineages. The results showed that Lactuca species are generally similar in plastome size, GC content, gene structure and categories, although crop lettuce (Lactuca sativa L.) and its gene pool relatives were found to have one unique pseudogene (ψ ndhF) and accD, atpF, cemA, clpP and rpl22 showed signs of positive selection. Our phylogenomic analysis demonstrated that Lactuca is monophyletic after excluding Lactuca alatipes Collett & Hemsl and AE Lactuca species. AE Lactuca species are morphologically distinct from core Lactuca lineage and need to excluded from Lactua. The core Lactuca species most likely originated from Asia-Temperate W ~ 6.82 Mya, and then dispersed globally and formed nine clades. Finally, the lettuce gene pool concept was amended according to the phylogenetic and historical biogeographic analyses. This study revised the circumscription of Lactuca, revealed robust phylogenetic relationships within the genus, and provided insights into Lactucinae phylogeny. The lettuce gene pool species could be used as potential genetic resources for lettuce breeding.